The Status of Creative Writing in Jordanian Universities from the Viewpoint of Students and Faculty Members - Alqam, Sabhah Ahmad; Hleiban, Tahaweel Atallah; Abu Kushk, Zahirah Tawfeeq (Dirasat: Human and Social Sciences, 2023)
Objectives: The study attempts to elucidate the status of creative writing in Jordanian Universities from the viewpoint of students and faculty members. Methods: The study is conducted on (385) male and female students and (255) faculty members from selected Jordanian universities using the stratified random sampling method. The sample members responded to two questionnaires; one is for faculty members and the other is for students. The study adopts the descriptive method approach which describes and analyzes the studied phenomenon under investigation and presents its results. Results: According to both students and faculty members, the study's findings indicate that university students' creative writing skills are on the medium level range. Additionally, it demonstrates that there are no statistically significant differences between students and faculty members based on their gender, but that there are significant statistical differences based on the academic year, in favor of fourth-year students, the type of university, in favor of public universities, and the rank of the faculty member, favoring associate professors. Conclusionss: The study recommends the necessity of creating and adopting a clear and a well-organized approach as part of obligatory university courses in creative writing in public and private universities taught by specialized professors in this field.